All contraries confounded : the lyrical fiction of Virginia Woolf, Djuna Barnes, and Marguerite Duras - Kaivola, Karen, 1957- (University of Iowa Press, 1991)
This insightful volume extends feminist critical studies of twentieth-century women writers as it examines the complex ways female subjectivity experiences and is shaped by gender and power in literary texts. Because of the ways ambivalence and contradiction operate in the works of Woolf, Barnes, and Duras, to read them is to able to interrogate and thus more fully understand the ways our own subjectivity are constructed in relation to complex configurations of desire, loss, sexuality, power, vulnerability, and violence. Kaivola has worked out a strikingly original means of reading difference-